Framing Analysis of Typo News Reports on Job Creation Through Online News Media - Deska Rinanti Hayyattun Nuffuss; Sri Rohaningsih (Kanal: Jurnal Ilmu Komunikasi, 2021)
The ratification of the Job Creation Law in early November 2020 created a lot of polemics in the society, this leads the news in the online media to have their own views in reviewing typos related to the content in the Job Creation Act. This study aims to unravel the results of media framing from a certain topic by reviewing news coverage by two different online news channels in the same upload period on November 3rd, 2020. The news reconstruction of journalists' points of view creates a gap between empirical truth and public awareness so readers can follow the media thought. The framing analysis was carried out on two news channels, namely CNBC Indonesia and Nasional Tempo, which reported typos in the writing of the Job Creation Law from a different point of view. The method used in this study is from Zhongdang Pan and Gerald M. Kosicki framing analysis model using four structures, namely Syntax, Script, Thematic, and Rhetorical. The results of this study indicate that media coverage of CNBC Indonesia tends to be in line with the government, while the Tempo National media constructs news coverage with a more critical tone. Additionally, other factors in the form of ownership and interests could also affect news framing. This is based on the fact that there is a trend of media conglomeration in Indonesia which can have certain implications for the news content.